2021
DOI: 10.1016/j.jtumed.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of platelet-rich fibrin on post-surgical complications following removal of impacted wisdom teeth: A pilot study

Abstract: Objectives Platelet-rich fibrin (PRF) is a fibrin matrix composed of cells, cytokines, and growth factors, which may be liberated from blood at specific times and act as a resorbable membrane. Many studies have demonstrated the benefits of PRF for bone healing in oral and maxillofacial implant surgery. Our study assesses the impact of PRF on postoperative complications following the extraction of impacted wisdom teeth. Methods Twenty patients were recruited in this blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The research group co-cultured MC with human bone marrow mesenchymal stem cells in the early stage to confirm the osteogenic properties of MC. PRF developed by Choukroun 32) is a secondgeneration biomaterial obtained by centrifugation of autologous blood, rich in platelets and leukocytes, and acts as a fibrin scaffold and a modulator of various cytokines, producing fibrin and cell migration, promoting tissue healing 33) . Numerous studies have shown that PRF can gradually release its cytokines and cells 34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…The research group co-cultured MC with human bone marrow mesenchymal stem cells in the early stage to confirm the osteogenic properties of MC. PRF developed by Choukroun 32) is a secondgeneration biomaterial obtained by centrifugation of autologous blood, rich in platelets and leukocytes, and acts as a fibrin scaffold and a modulator of various cytokines, producing fibrin and cell migration, promoting tissue healing 33) . Numerous studies have shown that PRF can gradually release its cytokines and cells 34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have revealed that while it promotes the formation of osteoblasts, gingival fibroblasts, and periodontal ligament cells, it suppresses the growth of oral epithelial cells [ 69 - 71 ]. PRF may help heal periodontal osseous abnormalities [ 72 ] because it can regulate the expression of phosphorylated extracellular signal-regulated protein kinase [ 73 , 74 ] and prevent osteoclastogenesis by inducing the formation of osteoprotegerin in the bone [ 73 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-extraction bleeding was assessed on a five-point scale, with grade 0 indicating no bleeding; grade I indicating very mild bleeding; grade II indicating mild bleeding; grade III indicating moderate bleeding, and grade IV indicating severe bleeding [ 12 ].…”
Section: Methodsmentioning
confidence: 99%